Mapping of Novel Leaf Rust and Stem Rust Resistance Genes in the Portuguese Durum Wheat Landrace PI 192051. Issue 8 (1st August 2019) - Aoun, Meriem; Kolmer, James A; Rouse, Matthew N; Elias, Elias M; Breiland, Matthew; Bulbula, Worku Denbel; Chao, Shiaoman; Acevedo, Maricelis
Abstract: Leaf rust caused by Puccinia triticina Erikss. ( Pt ) and stem rust caused by Puccinia graminis f. sp. tritic i Erikss. & E. Henn ( Pgt ) are serious constraints to production of durum wheat ( Triticum turgidum L). The objective of this study was to identify leaf rust resistance ( Lr ) and stem rust resistance ( Sr ) genes/QTL in Portuguese durum landrace PI 192051. Four Pt -isolates, representing three virulence phenotypes (BBBQJ, BBBSJ & EEEEE) and six Pgt -races TTKSK, JRCQC, TKTTF, QFCFC, TPMKC and TMLKC were used to evaluate 180 recombinant inbred lines (RILs) derived from the cross Rusty (rust susceptible) × PI 192051-1 (rust resistant) at the seedling stage. The RILs were also phenotyped at the adult-plant stage in a stem rust nursery in Ethiopia in 2017. The RILs were genotyped using the Illumina iSelect 9K wheat SNP array. PI 192051-1 carries a previously unidentified major Sr gene designated as QSr.ace-7A on chromosome arm 7AS and Lr gene Lr.ace-4A in the pericentromeric region of chromosome 4A. In addition, three minor Sr QTL QSr.ace-1A, QSr.ace-2B and QSr.ace-4A were mapped in PI 192051-1 on chromosomes 1AL, 2BL, and 4A, respectively Lr.ace-4A could be co-located or tightly linked to QSr.ace-4A . Markers linked to the identified QTL/genes can be used for marker assisted selection. These findings enrich the genetic basis of rust resistance in both durum and common wheat.